Controllable Dynamic Zigzag Pattern Formation in a Soft Helical Superstructure. Issue 30 (7th June 2017) - Zheng, Zhi‐gang; Zola, Rafael S.; Bisoyi, Hari Krishna; Wang, Ling; Li, Yannian; Bunning, Timothy J.; Li, Quan
Abstract : Zigzag pattern formation is a common and important phenomenon in nature serving a multitude of purposes. For example, the zigzag‐shaped edge of green leaves boosts the transportation and absorption of nutrients. However, the elucidation of this complicated shape formation is challenging in fluid mechanics and soft condensed matter systems. Herein, a dynamically reconfigurable zigzag pattern deformation of a soft helical superstructure is demonstrated in a photoresponsive self‐organized cholesteric liquid crystal superstructure under the simultaneous influence of an applied electric field and light irradiation. The zigzag‐shaped pattern can not only be generated and terminated repeatedly on demand, but can also be easily manipulated by alternating irradiation of ultraviolet and visible light while under the influence of a sustained electric field. This unique behavior results from a delicate balance among the variable experimental parameters. The evolution of the zigzag‐shaped pattern is successfully modeled by numerical simulations and has been monitored through diffraction of a probe laser. Interestingly, this fascinating zigzag‐shaped pattern yields crescent‐shaped diffraction pattern. The reversibly controllable dynamic zigzag pattern could enable the fabrication of novel photonic devices and architectures, besides greatly advancing the fundamental understanding of temporal behavior of ordered soft materials under combined stimuli. Abstract : Controllable dynamic zigzag‐shaped pattern formation in a photoresponsive soft self‐organized helical superstructure is accomplished via the coupled stimuli effect of electric field and light, which has enabled a unique diffraction pattern not found before.